Introduction to the Special Issue: Multispecies security and personhood. Issue 2 (April 2023) - Leep, Matthew
Abstract: The contributions to this Special Issue examine multispecies perspectives on the political dynamics of international life. Building on this theme, I consider the complex and manifold ways in which the subject of security can be understood in terms of more-than-human personhood. First, by thinking of more-than-human animals as phenomenally conscious persons, we might better appreciate the multispecies complexity of security as an agentic and affective experience. Second, attending to the spiritual character of certain indigenous articulations of personhood presses us to decipher how spiritual claims might inform moral and legal dimensions of multispecies security-seeking behaviour. To illustrate the significance of these moves, I first draw on more-than-human experiences of war, pathogenic viruses, and the global factory farm. I then explore conceptions of spiritual personhood in the context of Ojibwe responsibilities to protect wolves. These perspectives on personhood demonstrate possibilities for cultivating greater interest in the multispecies experience of security.